2017
DOI: 10.1016/j.bbr.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Microglia depletion in early life programs persistent changes in social, mood-related, and locomotor behavior in male and female rats

Abstract: Microglia, the innate immune cells of the central nervous system, regulate brain development by promoting cell genesis, pruning synapses, and removing dying, newly-born or progenitor cells. However, the role of microglia in the early life programming of behavior under normal conditions is not well characterized. We used central infusion of liposomal clodronate to selectively deplete microglia from the neonatal rat brain and subsequently assessed the impact of microglial depletion on programming of juvenile and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 69 publications
6
79
0
1
Order By: Relevance
“…Conspecific recognition is one aspect of a social interaction, and further studies are needed to examine whether the observed social impairments extend to more complex social behaviors. Along these lines, a recent report in rats found that neonatal microglia depletion induced minor deficits in juvenile play behavior and increased social avoidance in adulthood (Nelson and Lenz, 2016), consistent with our findings here.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Conspecific recognition is one aspect of a social interaction, and further studies are needed to examine whether the observed social impairments extend to more complex social behaviors. Along these lines, a recent report in rats found that neonatal microglia depletion induced minor deficits in juvenile play behavior and increased social avoidance in adulthood (Nelson and Lenz, 2016), consistent with our findings here.…”
Section: Discussionsupporting
confidence: 93%
“…To this point, in pilot studies and the data presented here, nearly 20% of microglia-depleted animals jumped off of the elevated plus maze during the test and continued to explore the testing room. One such animal ended the test in this manner in fewer than 5 s. Our findings are strikingly similar to those of Nelson and Lenz (2016), who found increased locomotion and decreased anxiety-like behavior in the open field and elevated plus maze, even observing comparable numbers of animals that jumped off the elevated plus maze open arms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The FST was conducted to assess behavioral despair in a sound-attenuated room, which was dimly illuminated 14. Rats were placed individually in a clear plastic cylinder (height =40 cm; diameter =30 cm) filled with water to 21.5±1.5 cm high at 24°C±0.5°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, masculinization of copulatory behaviour in females by neonatal oestradiol treatment can be prevented by co-treatment with minocycline 43 . Even brief microglial ablation from the neonatal brain of males leads to complete loss of male typical copulatory behaviour in adulthood 52 , along with other sex-specific effects 53 .…”
Section: Mechanisms Of Sexual Differentiationmentioning
confidence: 99%